Experiences from Implementing a Mobile Multiplayer Real-Time Game for Wireless Networks with High Latency. (10th December 2009) - Wang, Alf Inge; Jarrett, Martin; Sorteberg, Eivind
Abstract : This paper describes results and experiences from designing, implementing, and testing a multiplayer real-time game over mobile networks with high latency. The paper reports on network latency and bandwidth measurements from playing the game live over GPRS, EDGE, UMTS, and WLAN using the TCP and the UDP protocols. These measurements describe the practical constraints of various wireless networks and protocols when used for mobile multiplayer game purposes. Further, the paper reports on experiences from implementing various approaches to minimize issues related to high latency. Specifically, the paper focuses on a discussion about how much of the game should run locally on the client versus on the server to minimize the load on the mobile device and obtain sufficient consistency in the game. The game was designed to reveal all kinds of implementation issues of mobile network multiplayer games. The goal of the game is for a player to push other players around and into traps where they loose their lives. The game relies heavily on collision detection between the players and game objects. The paper presents experiences from experimenting with various approaches that can be used to handle such collisions, and highlights the advantages and disadvantages of the various approaches.